ON THE COASE THEOREM AS A THEORETICAL BASIS FOR THE KYOTO AND PARIS PROTOCOLS - Egorov, Dmitry; Manoilova, Marina; Strakhov, Vasilii; Egorov, Gleb (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Purpose of the study: a critical examination of the so-called Coase theorem, which is largely the theoretical basis of the idea of trading in emission quotas for greenhouse gas emissions. Since the research is theoretical, research methods: critical analysis of texts written by researchers who adhere to the economic mainstream and theoretical construction. In our opinion, Coase's theorem is essentially reduced to indicating that two conditions are implicitly assumed in the proof of the optimality of the ideal market model: 1) the absence of transaction costs; 2) fully defined property rights to all resources, in any way involved in the transactions in question. The problem is that these two conditions in a situation of environmental problems are completely unrealistic. Therefore, the question of optimal environmental and economic regulation cannot be considered closed. Moreover, it is impossible to present this problem as already solved when writing textbooks for students and graduate students. Those who study must be aware of the real complexity of the problem of unwanted externalities destroying the Earth's biosphere. Only in this case, having become managers and politicians, they will be able to stop negative processes in the biosphere and implement the declarations adopted in Rio de Janeiro, Kyoto and Paris in the common interests of all people living on Earth.